Validation of the Optimal Points of Tribological Systems at Different Temperatures Determined by the DOE Method Using Lubricating Oil Doped with Nano-ZrO2 Particles - Ádám I. Szabó; Kevin Szabó (Engineering Proceedings, 2024)
In this study, the design of experiments (DOE) method is used to find the optimum values of the tribological system in a 40–120 °C range with 0.1–1 wt% zirconia nanoadditives in a base oil. Significant factors were identified. The studied parameters include friction absolute integral, static friction, the wear scar diameter and the wear volume of the specimens. The measurements were carried out on a tribometer. The results were pre-estimated using statistical software; then, validation measurements were made using the estimated optimum point. The results show that the FAI value differed by 0.008, the COF value by 0.017, the WSD value by 4 μm and the WV value by 110,000 μm3. At 1 wt%, zirconia can have a positive effect at high temperatures. As temperatures increase, wear parameters decrease and friction values remain stable.